Intermediaries and Innovation: Why they emerge and how they facilitate IP transactions on the markets for technology - Frank Tietze; Cornelius Herstatt (Hamburg University of Technology (TUHH), Institute for Technology and Innovation Management (TIM), 2009)
With this paper we aim to contribute to the discussion about the difficulties that occur when trading technical knowledge and particularly patents. Currently one can observe that markets for technology have been sizable growing, transaction obstacles are still immanent and technology market intermediaries (TMI) emerge that develop new models aiming to facilitate Intellectual Property (IP) transactions. Why TMIs emerge and how they attempt to facilitate IP transactions however is not yet sufficiently understood. We propose theoretical explanations for these two questions building primarily on the contributions of Stigler (1951) and Williamson (1979). We argue that the growing markets for technologies on the one hand and immanent transaction obstacles on the other hand lead to further division of labor and thus foster the emergence of TMIs. Following Williamson (1979) we propose that the new transaction models developed by TMIs attempt to implement more standardized governance structures in order to diminish transaction costs. However it remains to be seen which of the newly developed models (or those to come) will survive and actually deliver more economic transactions.
Keywords: 650